1982
DOI: 10.1093/oxfordjournals.aje.a113293
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Coronary Heart Disease in Siblings—a Multivariate Assessment

Abstract: The incidence of clinically recognized coronary heart disease and its relation to risk factors have been studied for 596 sibships in the Framingham Heart Study cohort. Only the 186 pairs of brothers were considered in the multivariate analysis, since the rate of coronary heart disease in women is low. Multiple logistic regression was performed by using endpoints of coronary heart disease as the dependent variable for the younger brother of the pair. Age, Metropolitan relative weight, systolic blood pressure, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(33 citation statements)
references
References 0 publications
1
29
1
2
Order By: Relevance
“…Family history of coronary artery disease (FHxCAD) is an established risk factor for the development of acute myocardial infarction (AMI) (1). However, data relating to impact of FHxCAD on post-ST-segment myocardial infarction (STEMI) clinical outcomes is limited (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Family history of coronary artery disease (FHxCAD) is an established risk factor for the development of acute myocardial infarction (AMI) (1). However, data relating to impact of FHxCAD on post-ST-segment myocardial infarction (STEMI) clinical outcomes is limited (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Several studies have shown that family history (FHx) of CAD is strongly associated with incident cardiovascular disease, independent of traditional risk factors, and improves risk assessment. [4][5][6][7][8] Recently, genetic risk scores (GRSs) for CAD, consisting of specific genetic variants identified from genome-wide association studies, have also been associated with incident cardiovascular disease and have shown promise in improving cardiovascular risk prediction. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the exact predisposing mechanisms that account for the increased risk in patients with a FHx or a high GRS remain unclear.…”
mentioning
confidence: 99%
“…A recent study by Snowden et al 141 showed the concordance of CHD among the siblings of the Framingham Heart Study. The incidence of Ml in the older brothers was significantly related to the Ml experience of the younger brothers, even after the effects of total cholesterol, systolic blood pressure, and cigarette smoking were controlled in a multivariate analysis.…”
Section: Genetics and Multiple Risk Factorsmentioning
confidence: 98%